2019
DOI: 10.1016/j.toxrep.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary thrombosis in acute organophosphate poisoning—Case report and literature overview of prothrombotic preconditioning in organophosphate toxicity

Abstract: Highlights Acute OP poisoning complicated with pulmonary thrombosis during the first week of poisoning. Antidote treatment included atropine, whereas diazepam was administered in the first 48 h. There was no administration of oximes due to unavailability. Prolonged hypoxemia in acute OP intoxication indicates exclusion of thrombotic pulmonary event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Moreover, it was noticed that most of the pulmonary blood vessels showed atrophy and loss of the media and endothelial cells, respectively. This might clarify the thrombotic activity of the organophosphorus compounds 49 . The adverse effect of the malathion inhalation was mitigated by TQ supplementation in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, it was noticed that most of the pulmonary blood vessels showed atrophy and loss of the media and endothelial cells, respectively. This might clarify the thrombotic activity of the organophosphorus compounds 49 . The adverse effect of the malathion inhalation was mitigated by TQ supplementation in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 93%
“…The leading maxim in the treatment of AOPP intoxication should, therefore, be “treat the patient, not the poison” [ 13 ], as has been successfully practiced in recently published case reports [ 164 , 167 , 168 , 169 , 170 ]. Elevated serum levels of inflammation markers in combination with hypoalbuminemia must be interpreted more as signs of tissue ischemia caused by hypovolemia than as direct consequences of the reduced acetylcholine degradation at the neuronal level.…”
Section: Discussionmentioning
confidence: 99%
“…The proper interpretation of the origin and significance of markers of tissue damage such as increased levels of C-reactive protein, fibrinogen, lactate, amylase [ 165 ] or serum troponin level and other markers of cardiac damage [ 166 ] in combination with hypoalbuminemia is of crucial importance in guiding treatment of the “secondary” effects of acute AOPP ( Figure 1 ) if we wish to improve survival in such patients [ 167 , 168 , 169 , 170 ] after decades of therapeutic stagnation [ 171 , 172 , 173 ].…”
Section: Acetylcholinesterase and Albumin Measurement: Importance For...mentioning
confidence: 99%
“…A recent report has also been published of pulmonary thrombosis in acute organophosphate poisoning. (11) Another case of OP poisoning presenting with clinical features of coronary thrombosis and pulmonary thromboembolism has been reported that occurred during the delayed phase. (12) A rare case of upper extremity deep vein thrombosis in OP poisoning has also been published.…”
Section: Discussionmentioning
confidence: 99%